Writing in Limbo Modernism and Caribbean Literature - Gikandi, Simon (Cornell University Press, 1992)
In Simon Gikandi's view, Caribbean literature and postcolonial literature more generally negotiate an uneasy relationship with the concepts of modernism and modernity-a relationship in which the Caribbean writer, unable to escape a history encoded by Europe, accepts the challenge of rewriting it. Drawing on contemporary deconstructionist theory, Gikandi looks at how such Caribbean writers as George Lamming, Samuel Selvon, Alejo Carpentier, C. L. R. James, Paule Marshall, Merle Hodge, Zee Edgell, and Michelle Cliff have attempted to confront European modernism. ; In Simon Gikandi's view, Caribbean literature and postcolonial literature more generally negotiate an uneasy relationship with the concepts of modernism and modernity-a relationship in which the Caribbean writer, unable to escape a history encoded by Europe, accepts the challenge of rewriting it. Drawing on contemporary deconstructionist theory, Gikandi looks at how such Caribbean writers as George Lamming, Samuel Selvon, Alejo Carpentier, C. L. R. James, Paule Marshall, Merle Hodge, Zee Edgell, and Michelle Cliff have attempted to confront European modernism.